Antagonistic Effect of Endophytic Fungal, Fusarium sp. MFLUCC16-1462, Against Magnaporthe oryzae - Pripdeevech, Patcharee; Tanapichatsakul, Chutima; Chimthai, Surangkana; Phormmard, Witthawad; Brooks, Siraprapa; Athinuwat, Dusit (Thai Journal of Science and Technology, 2018)
Abstract Sixty-six fungal endophytes were isolated from the leaves of Litsea petiolata Hook. f. collected in Chiang Rai, Thailand. Crude extracts obtained from macerated endophytic fungi with ethyl acetate were used to screen their antifungal activity against two isolates (THL084 and THL861) of rice blast disease, Magnaporthe oryzae. Based on disc diffusion assay, crude extract of Fusarium sp. MFLUCC16-1462 exhibited antifungal activity against the THL084 isolate. The extract also greatly reduced the growth of the THL084 isolate. At 96 h after dual cultures with the Fusarium sp. MFLUCC16-1462, mycelium growth of THL084 and THL 861 was inhibited 61.96 and 31.74 %, respectively. The chemical composition of the fungal extract was further identified using a gas chromatographic-mass spectrometric method with their retention indices. Seventy constituents representing 95.92 % of the crude extract were identified. Major components were pregeijerene B, callitrin, drimenol, b-calacorene, benzyl acetylacetate and angustione. Antifungal activity of crude extract Fusarium sp. MFLUCC16-1462 could be involved to a combination of chemical constituents such as pregeijerene B, callitrin, drimenol, angustione, Z-lanceol acetate, nor-davanone, 1,4-cineole and 1,8-cineole. These active components could damage cellular membrane and leakage inhibiting spore germination, proliferation, and cellular respiration. It was indicated that the endophytic fungus Fusarium sp. MFLUCC16-1462 may suggest an evolutionarily important role for endophytic fungi, associating L. petiolata leaves, against fungal plant pathogens, and could be used in agricultural management in the future. Keywords: biological control; blast; rice disease control; endophytic fungi